Perspektif Hukum Islam terhadap Jual Beli Hak Arisan di Desa Kropoh Sumenep - Hali Makki (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2017)
Historically buying and selling is an existing custom of both Muslim and non-Muslim, of course, buying and selling has a very binding regulations that can be used as the foundation for people who will buy a contract. seller and buyer need to submit on requisites and principles of buying and selling, while the law will provide protection that covers requisites and principles of buying and selling. The practice of buying and selling the claim of social gathering (arisan) in the Kropoh village invalid because it has fulfilled the regulations of buying and selling.